Coming Home to Modern Japan. An Orphic Dialogue between Japan and the West in Murakami Haruki’s Norwegian Wood - Emiel Nachtegael (IAFOR Journal of Literature & Librarianship, 2013)
This article addresses the debate on the "Japanese identity" of Norwegian Wood, which — though popular — is often conducted in an intuitive fashion. I try to find a way out by looking more thoroughly into the Orphic legacy of the novel than has been done up to now by Japanese scholars. First of all, my purpose is to extend the intertextual reading by bringing into the equation the Japanese version of the Orpheus tale. A comparative analysis can thus trace the author’s more-or-less unconscious cultural influences from Japan (the myth of Izanagi) and the West (Orpheus). Furthermore, I take into account the novel’s love triangles, which connect the two intertexts. In short, I see the novel’s identity as a transformative one. Murakami’s Orpheus — the lovestricken Tōru — tracks across the Greek/Western parameters of the Orphic myth (i.e., the triumph of death and individuality) after his descent into the "Underworld" of Ami Hostel but finally sails back to Japanese home waters, as it were, when he decides to look forward to life and love (Midori). Choosing connectedness over alienation like Izanagi, the protagonist of Norwegian Wood — and arguably its dislocated author — leave behind the tempting but disillusioning Western culture. Both achieve this however thanks to one crucial element which is lacking in the Japanese myth and represented in the novel by Reiko: the wondrous power of music/art. The latter is Murakami’s Golden Fleece brought back from the West. Finally I discuss how this enriched state of mind may have altered Murakami’s "vague, Japanese" fictional "I".